PINDIT: an Online Digital Signage at Department of Electrical Engineering, University of Riau - Nasution, Salhazan; Syachrodi (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
Digital information boards are widely used for displaying one-way information and announcements in a fast, precise, and up-to-date manner. In the Department of Electrical Engineering University of Riau, the media used to convey information and announcements is still conventional, which is using wall magazines and banners. This study aims to build a digital information board or Papan Informasi Digital (PINDIT), a web-based information system that will be displayed on a monitor screen or LED TV and placed in front of the Electrical Engineering office. The academic community or visitors can easily access information or announcements related to campus activities through these digital information boards. Information on PINDIT can be updated by administrators from anywhere via the internet and displayed in real-time. PINDIT uses Rasberry Pi as a device that connects the information system with the LED TV screen, it also equipped with an RFID device which is used as a tool to record lecturers' attendance status in the room. We conducted Usability Testing for PINDIT on 33 respondents using the USE Questionnaire with aspects of learnability, efficiency, memorability, errors, and satisfaction. From the overall test results, PINDIT can be categorized as